2006
DOI: 10.1021/bi061489x
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrolase and Transferase Activity of an Inverting Mutant Sialidase Using Non-natural β-Sialoside Substrates

Abstract: The Y370G inverting mutant sialidase from Micromonospora viridifaciens possesses beta-sialidase activity with phenyl beta-sialoside (Ph-betaNeuAc) to give alpha-sialic acid as the first formed product. The derived catalytic rate constants for k(cat) and k(cat)/K(m) are 13.3 +/- 0.3 and (2.9 +/- 0.3) x 10(5) M(-)(1) s(-)(1), respectively. This enzyme is highly specific for the phenyl substrate, with substituted phenyl and thiophenyl leaving groups having k(cat) values that are at least 1000-fold lower. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 34 publications
(81 reference statements)
3
22
0
Order By: Relevance
“…The only previous reports of inverting sialidases are those describing mutant enzymes, wherein the catalytic tyrosine nucleophile of a retaining sialidase has been mutated to an alanine (70,75,76). Removing the nucleophilic catalyst resulted in a switch from a retaining mechanism in the wild type sialidase to an inverting mechanism in the mutant.…”
Section: Discussionmentioning
confidence: 99%
“…The only previous reports of inverting sialidases are those describing mutant enzymes, wherein the catalytic tyrosine nucleophile of a retaining sialidase has been mutated to an alanine (70,75,76). Removing the nucleophilic catalyst resulted in a switch from a retaining mechanism in the wild type sialidase to an inverting mechanism in the mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Sialidases employ a nucleophilic Tyr instead of the more common Asp/Glu. Not being actual glycosynthases, mutations of this nucleophilic Tyr in Micromonospora viridifaciens sialidase (EC 3.2.1.18; GH 33) resulted in a number of mutants that retained hydrolytic activity with either retention or inversion of configuration. , Using phenyl β- d -sialic acid as a donor, the inverting mutant Y370G catalyzed production of sialyl-lactose with a yield of 13%, with >90% being the α­(2,6)-isomer and with no subsequent product hydrolysis …”
Section: Protein Engineeringmentioning
confidence: 99%
“…111,112 Using phenyl β-D-sialic acid as a donor, the inverting mutant Y370G catalyzed production of sialyl-lactose with a yield of 13%, with >90% being the α(2,6)-isomer and with no subsequent product hydrolysis. 113 However, it follows that glycosynthase catalysis releases either hydrofluoric acid (HF) or hydrazoic acid (HN 3 ) as its byproduct. Although numerous methods for the removal of fluoride ions from aqueous solution exist, 114 this issue of removal has hardly been addressed by any of the otherwise thorough reviews (see, e.g., refs 103, 105, and 106) of glycosynthases and the use of glycosyl fluorides as substrates.…”
Section: ■ Protein Engineeringmentioning
confidence: 99%
“…Despite the observed success with the use of S-glycosides as inhibitors of glycosidases including sialidases (Watson et al, 2006) the Neu5Acα2-3-S-Galβ- O -octyl was found to show no significant inhibition of TcTS even at millimolar concentrations (Harrison et al, 2001). The low inhibition rates observed by the Neu5Acα2-3-S-Galβ- O -octyl suggest that the conformations acquired by this compound in solution might not be recognized by the TcTS.…”
Section: Inhibition Of Sialic Acid Transference By Tctsmentioning
confidence: 99%